Analisis Kualitas Layanan Berbasis RATER dan Dampaknya terhadap Kepuasan Tamu dan Arus Kas Operasional pada Ancyra by Continent Poso - Waldiyono Waldiyono; Agus Solikhin; Alip Suroto; I Gusti Ayu Agung (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study examines the association between RATER-based service-quality perceptions and net operating cash flow at Ancyra by Continent Poso. A quantitative explanatory design used questionnaire data from 100 hotel guests and operating cash-flow data aggregated into 12 periods. Questionnaire responses were used to describe respondents and assess the instrument, whereas inferential analysis used 12 period-level pairs of aggregate RATER scores and net cash. The seven-item instrument showed item-total correlations of 0.310–0.485 and high internal consistency (Cronbach’s Alpha = 0.882). Mean indicator scores ranged from 4.51 to 4.67, and all 12 periods recorded positive net operating cash flow. At N = 12, correlations between individual RATER indicators and net cash were positive but not statistically significant. Simple regression produced R = 0.300, R² = 0.090, adjusted R² = −0.001, F(1,10) = 0.989, and p = 0.343; therefore, H1 was not supported. The findings describe favorable service-quality perceptions and positive operating cash flow but do not provide sufficient statistical evidence of a consistent association between the two variables. The study contributes methodologically by aligning individual customer data with organization-level financial data and highlights the need for longer longitudinal series and relevant operational controls.